2015
DOI: 10.1186/s12893-015-0098-x
|View full text |Cite
|
Sign up to set email alerts
|

Autotransplantation of parathyroid grafts into the tibialis anterior muscle after parathyroidectomy: a novel autotransplantation site

Abstract: BackgroundSurgical management of renal secondary hyperparathyroidism (sHPT) is varying. Total parathyroidectomy with heterotopic autotransplantation (TPTX + AT) is one of the standard surgical procedures in sHPT, but there is no consensus about the optimal site for graft insertion. At the surgical department of the University Hospital of Heidelberg we prefer the autotransplantation into the tibialis anterior muscle. The aim of this study was to assess the long-term function of the auto-transplanted parathyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…After resection, tPTX + AT required another procedure: AT. The sites used for AT were the sternocleidomastoid muscle, brachioradialis muscle and tibialis anterior muscle [20,28,29]. Most surgeons chose the brachioradialis muscle for AT because this site is simple for reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…After resection, tPTX + AT required another procedure: AT. The sites used for AT were the sternocleidomastoid muscle, brachioradialis muscle and tibialis anterior muscle [20,28,29]. Most surgeons chose the brachioradialis muscle for AT because this site is simple for reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental group involves the participants with PA at the novel sites closer to the cephalic vein, while the participants in the control group generally receive subcutaneous transplantion. Since the survival rate of the traditional assessing method was reported as 45% [16], and that of the new method was predicted as 65% in our preliminary study (unpublished data). We set α as 0.05 (bilateral), power as 0.90 and obtained the sample size N 1 = N 2 = 128 by PASS 11.…”
Section: Methodsmentioning
confidence: 93%
“…It was mostly applied to monitor PTH in hyperparathyroidism patients with parathyroidectomy after PA [13, 14]. Rothmund et al reported that the survival rate of PA with hyperparathyroidism was 31% (20 patients) [15], and Anamaterou et al suggested that the survival rate was 45% in 19 patients using the ischemic-blockage Casanova test [16]. There are few reports regarding randomized controlled trials to evaluate the function of transplanted parathyroid glands using this PTH-gradient method.…”
Section: Introductionmentioning
confidence: 99%
“…In the event of recurrent hyperparathyroidism, it is generally easy to determine if the forearm graft is the cause based on parathyroid scanning, through selective venous sampling, or using a limb ischemia test which should result in substantial reduction of PTH after 15 min of ischemia if the forearm graft is indeed the cause of recurrent disease [ 7 ]. There are numerous documented graft locations such as the neck, abdomen, pre-sternal area, or the leg [ 8 – 10 ]. While these locations may be less likely to generate misleading blood test results as they are remote from common blood-drawing locations, there can be disadvantages to these sites such as an inability to perform some of the aforementioned localization and functional testing, more difficult surgical accessibility for removal, concerns regarding leg wound healing in patients with circulatory disease, and cosmesis.…”
Section: Discussionmentioning
confidence: 99%